2021
DOI: 10.3389/fnut.2021.765809
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Glutamine on Immune Function and Post-Operative Complications of Patients With Colorectal Cancer

Abstract: The aim of this meta-analysis was to evaluate the clinical significance of glutamine in the management of patients with colorectal cancer (CRC) after radical operation. Electronic databases, including PubMed, EMBASE, MEDLINE, Cochrane Library, Chinese Biomedical Database (CBM), China National Knowledge Infrastructure (CNKI), VIP medicine information system (VIP), and Wanfang electronic databases were comprehensively searched from inception to 30, July 2021. Prospective randomized trials with glutamine vs. rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 68 publications
1
17
0
2
Order By: Relevance
“…En una revisión sistemática y metaanálisis publicada en el 2019, donde se incluyeron 19 ensayos clínicos con 1387 pacientes, se demostró que en aquellos pacientes que van a cirugía electiva por cáncer gastrointestinal, el uso de la IMN con glutamina enteral perioperatoria disminuyó el riesgo de las complicaciones posoperatorias (formación de fístulas e infecciones) un 48% (RR 0,52; IC 95% 0,38-0,71), también hubo una disminución en los días de la estancia hospitalaria (1,57 días, IC 95% -2,48, -0,66) (9) . Otro metaanálisis, publicado en el 2021 por Yang y colaboradores (16) , con 31 ensayos controlados aleatorizados (ECA) y 2201 pacientes, demostró que el uso de la glutamina perioperatoria en pacientes con cáncer colorrectal mejoraba la respuesta humoral CD4 (DE = 0,76, IC 95% 0,53-0,99), inmunoglobulina (Ig) G (DE = 1,10; IC 95% 0,70-1,50); por otro lado, se demostró una menor estancia hospitalaria (DE = -1,13; IC 95% -1,68 a -0,58 días), así como menor riesgo de fuga de la anastomosis (RR = 0,23; IC 95% 0,09-0,61).…”
Section: Cicatrización De Heridas Síntesis De Proteínasunclassified
“…En una revisión sistemática y metaanálisis publicada en el 2019, donde se incluyeron 19 ensayos clínicos con 1387 pacientes, se demostró que en aquellos pacientes que van a cirugía electiva por cáncer gastrointestinal, el uso de la IMN con glutamina enteral perioperatoria disminuyó el riesgo de las complicaciones posoperatorias (formación de fístulas e infecciones) un 48% (RR 0,52; IC 95% 0,38-0,71), también hubo una disminución en los días de la estancia hospitalaria (1,57 días, IC 95% -2,48, -0,66) (9) . Otro metaanálisis, publicado en el 2021 por Yang y colaboradores (16) , con 31 ensayos controlados aleatorizados (ECA) y 2201 pacientes, demostró que el uso de la glutamina perioperatoria en pacientes con cáncer colorrectal mejoraba la respuesta humoral CD4 (DE = 0,76, IC 95% 0,53-0,99), inmunoglobulina (Ig) G (DE = 1,10; IC 95% 0,70-1,50); por otro lado, se demostró una menor estancia hospitalaria (DE = -1,13; IC 95% -1,68 a -0,58 días), así como menor riesgo de fuga de la anastomosis (RR = 0,23; IC 95% 0,09-0,61).…”
Section: Cicatrización De Heridas Síntesis De Proteínasunclassified
“…Meanwhile, glutamine transporter mutants have been shown to promote metabolic reprogramming of tumors [ 5 7 ]. Recent studies have shown that glutamine is also an important raw material for the immune system, and plays a major role in regulating lymphocyte functions such as, the release of secretory factors; proliferation; and their general maintenance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical outcomes in CRC have improved dramatically over the past 50 years, several factors may influence the result [8]. First, the high cellular turnover during tumorigenesis leads to a dysregulation of the host immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of malnutrition in CRC patients ranges from 45% to 60% and is significantly higher following radical surgery [10]. Together with the surgery-related impaired immune response, which induces a systemic inflammatory response syndrome, malnutrition accounts for most postoperative complications [8,11]. Complications, in turn, significantly worsen the short-term clinical results, length of stay (LOS) and hospital costs, impairing long-term oncological outcome and patient's quality of life [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation